Latin American Perspectives on the Global Commodity Chains Approach - Parada Gómez, Álvaro Martín (2018)
The analysis of global value chains (GVCs) as a theoretical and methodological framework has been widely used in academia (universities), in government for sectoral decision-making (ministries), and in the development of strategies to improve competitiveness (companies). From this perspective, the book Latin American Ideas on the Global Commodity Chain Approach, which will be discussed in this editorial, raises issues centered on multiple critical factors that affect productive sectors: quality, financing, international trade, and imperfect markets, among others.  The book was published by the National Autonomous University of Mexico Press and edited by Rafael Díaz Porras, Wim Peluppesy, and Pablo Pérez Akaki.